Effect of almond consumption on vascular function in patients with coronary artery disease: a randomized, controlled, cross-over trial. - Chen, C-Y. Oliver.; Holbrook, Monika.; Duess, Mai-Ann.; Dohadwala, Mustali M.; Hamburg, Naomi M.; Asztalos, Bela F.; Milbury, Paul E.; Blumberg, Jeffrey B.; Vita, Joseph A. (2016)
Objective: Almonds reduce cardiovascular disease risk via cholesterol reduction, anti-inflammation, glucoregulation, and antioxidation. The objective of this randomized, controlled, cross-over trial was to determine whether the addition of 85 g almonds daily to a National Cholesterol Education Program (NCEP) Step 1 diet (ALM) for 6 weeks would improve vascular function and inflammation in patients with coronary artery disease (CAD).; Keywords: Almonds, Coronary arterial disease, Dietary quality, Endothelial function, Inflammation, Oxidative stress.; Springer Open.